Harmful phytoplankton blooms and fish mortality in a eutrophicated reservoir of northeast Brazil - Chellappa,Naithirithi Tiruvenkatachary (2008)
The aim of this work was to study the eutrophication in the tropical freshwater ecosystems and the consequent cyanobacterial bloom formation and economical damage to fisheries and harmful effects to public health. Mass fish mortality due to toxin producing cyanobacterial blooms was registered during December 2003 in Marechal Dutra Reservoir, Acari/RN, Northeast Brazil. Phytoplankton and fish samplings were carried out on alternate days during the episode of fish mortality and monthly during January to June 2004. The cyanobacterial toxin was identified and quantified from the seston samples and liver of the dead fishes using the standard HPLC method. The results indicated that the toxic blooms of Cylindrospermopsis raciborskii and Microcystis aeruginosa were persistent for two weeks and represented 90% of the phytoplankton species assemblages. The lethally affected fishes were Oreochromis niloticus, Plagioscion squamosissimus, Cichla monoculus, Prochilodus brevis, Hoplias malabaricus and Leporinus friderici. The microcystin levels varied from 0.07 to 8.73µg L-1 the seston samples and from 0.01 to 2.59µg g-1in the liver samples of the fishes during the bloom period.